Establishing a Geriatric Hip Fracture Program at a Level 1 Community Trauma Center. (May 2020) - O'Mara-Gardner, Kristin; Redfern, Roberta E.; Bair, Jeffrey M.
Abstract : BACKGROUND: Traditional care of patients with geriatric hip fracture has been fragmented with patients admitted under various specialty services and to different units within a hospital. This produces inconsistent care and leads to varying outcomes that can be associated with increased length of stay, delays in time from admission to surgery, and higher readmission rates. PURPOSE: The purpose of this article is to describe the process taken to establish a successful geriatric hip fracture program (GFP) and the initial results observed in a single institution after its implementation. METHODS: All patients 60 years or older, with an osteoporotic hip fracture sustained from a low energy mechanism (defined as a fall from 3-ft height or less), were included in our program. Fracture patterns include femoral neck, intertrochanteric, pertrochanteric, and subtrochanteric femur fractures including displaced, nondisplaced, and periprosthetic fractures. Preprogram data included all patients admitted from January 1, 2012, through December 31, 2014; postprogram data were collected on patients admitted between May 1, 2016, and May 1, 2018. RESULTS: Demographic characteristics of the populations were similar. After the GFP was implemented, the proportion of patients who were treated surgically within 24 and 48 hours increased. The average number of hours between admission and surgery significantly reduced from 35.2 to 23.2 hours. Overall length of stay was decreased by 1.8 days and readmission within 30 days of discharge was lower. Reasons for readmission were similar in both timeframes. The rate of inpatient death was similar in the two groups. Mortality within 30 days of surgery appeared somewhat higher in the post-GFP period. CONCLUSION: Our program found that, with the utilization of a multidisciplinary approach, we could positively influence the care of patients with geriatric hip fracture through the implementation of evidence-based practice guidelines. In the first 2 years after initiation of the GFP, our institution saw a decrease in time from admission to surgery, length of stay, and blood transfusion requirements.